Caregivers Create a Veteran-Centric Community in VHA Medical Foster Homes. Issue 6 (17th August 2016) - Haverhals, Leah M.; Manheim, Chelsea E.; Gilman, Carrie V.; Jones, Jacqueline; Levy, Cari
ABSTRACT: The Veteran's Health Administration's Medical Foster Home program offers a unique long-term care option for veterans who require nursing-home- or assisted-living-level care. Veterans in a medical foster home reside with community-based caregivers who provide 24-hr-a-day care and monitoring. The veterans often remain in the medical foster home until end of life. Support and oversight is provided to the caregiver from the Veteran's Health Administration's community-based medical team. This qualitative descriptive study is based on secondary analysis of interviews with 20 medical foster home caregivers from 7 programs across the United States. The study's research aims are to describe and explain (a) the type of care backgrounds and skills these caregivers possess, (b) caregivers' primary motivations to open their homes to veterans who often have complex medical and social needs, and (c) how caregivers function in their role as primary caregiver for veterans. Findings indicated that caregivers interviewed had worked in long-term care settings and/or cared for family members. A strong desire to serve veterans was a primary motivation for caregivers, rather than financial gain. The caregivers' long-term care skills aided them in building and sustaining the unique medical foster home family-like community.